1980
DOI: 10.1001/archderm.116.10.1155
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fat necrosis of the newborn and idiopathic hypercalcemia. Report of a case

Abstract: A female infant who was anoxic at birth had lesions of subcutaneous fat necrosis at the age of 16 days. She also had problems with poor feeding, frequent vomiting, and failure to thrive. Hypercalcemia was discovered at the age of 28 days and she died at 11 1/2 weeks despite return of the serum calcium level to normal with oral prednisone therapy and a diet low in calcium and devoid of vitamin D. Fourteen other cases of idiopathic hypercalcemia in patients with subcutaneous fat necrosis of the newborn have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…SFN, no longer considered a localized form of SN, is an uncommon neonatal disorder appearing in infants born at term or post-term, frequently by cesarean section and with a history of fetal distress [11, 12, 13]. The clinical manifestations usually appear between the 1st and 4th week of life [11, 12, 13, 14, 15].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…SFN, no longer considered a localized form of SN, is an uncommon neonatal disorder appearing in infants born at term or post-term, frequently by cesarean section and with a history of fetal distress [11, 12, 13]. The clinical manifestations usually appear between the 1st and 4th week of life [11, 12, 13, 14, 15].…”
Section: Commentmentioning
confidence: 99%
“…The clinical manifestations usually appear between the 1st and 4th week of life [11, 12, 13, 14, 15]. To date, very few cases with lesions present at birth have been reported [16, 17, 18, 19, 20].…”
Section: Commentmentioning
confidence: 99%
“…1,[5][6][7][8][9][10][11][12][13][14] Complications related to hypercalcemia may be severe and have been implicated in the deaths of 3 infants. [10][11][12] Explanations offered for hypercalcemia include elevated parathyroid hormone levels, prostaglandin E 2 release, direct release of calcium from necrotic fat, or increased vitamin D activity. [12][13][14] However, the latter explanation is most widely accepted, and was likely responsible for the hypercalcemia documented in our patient.…”
Section: Critical Situations Commentmentioning
confidence: 99%
“…It generally affects healthy full-term infants, often those who have suf fered perinatal difficulties [ 1 ]. 11 is sometimes seen in post term infants [2,3].…”
Section: Case Reportmentioning
confidence: 99%
“…It has been suggested that hypercalcemia may be the result of the release of calcium from calcified necrotic subcutaneous fat [19], although it has been shown that diffuse soft tissue calcification can occur and resolve without evidence of hypercalcemia [20]. It has been proposed that hypercalcemia may be due to hyper sensitivity to vitamin D [21], or elevated parathyroid hor mone levels [1]. Autopsy studies, however, have not shown parathyroid hyperplasia [211.…”
Section: Case Reportmentioning
confidence: 99%